Uso do sensoriamento remoto e geoprocessamento no mapeamento de subzonas geoambientais das terras do município de Cujubim (RO), como subsídio a avaliação da aptidão agrícola. - Siane Cristhina Pedroso Guimarães; Jairo Roberto Jiménez-Rueda (Confins)
This text has as its main objective to perform the mapping of zones and subzones, considering the physical aspects of land of the Cujubim Municipality, situated in the state of Rondônia / Brazil, with the aim of contributing to the Assessment of Agricultural Suitability, using techniques of Remote Sensing and Geoprocessin. Were used as anchor satellite images in paper and digital format, which were stored and analysed in a Geographic Information System SPRING / INPE, which favoured the integration of data obtained during the work. The studied physical aspects provided information that enabled an assessment of environmental indicators which help on understanding the region as well, allowed to establish eco-dynamic conditions that are in balance / imbalance current. It also allows a better indication or orientation as to the occupation of the city studied, seeking to minimize and / or restore the environment in terms of support capacity of the analysed area. Thus, from the basic geographic data (drainage system, roads and altimetry), together with analysis and interpretation of satellite images, it was possible to evaluate and interpret the tectonic deformations showed that reflected on the surface, such as structural lineaments , fracture lines, lithology and morphostructure with the deformations of the type structural high and low. All this enabled an integrated synthesis, due to its ability used usability and relative to the degree of ability or restriction of land use.